The role of refuges in coral reef ecosystems and biological invasions - Boon, James (2025)
Refuges play a key role in mediating species interactions, influencing movement patterns and shaping ecological communities. As ecosystems worldwide face increasing pressure from anthropogenic activities, understanding how, and to what extent, refuges contribute to the persistence of biodiversity is crucial for effective conservation management. Using coral reef ecosystems and biological invasions as model systems, this thesis explores whether refuges fulfil their expected roles and how they directly and indirectly influence species behaviour and distribution. First, by reviewing scientific literature on biological invasions, I demonstrate that refuge-mediated processes influence the outcomes of non-native species introductions, revealing common patterns across terrestrial, marine, and freshwater ecosystems. Second, an investigation into depth refuges on coral reefs reveals that mesophotic fish communities have undergone greater compositional changes over time than those in shallower waters, which is inconsistent with the expectations of the deep reef refugia hypothesis. Third, I find no clear evidence that invasive lionfish undergo ontogenetic niche shifts from shallow to deeper waters. This suggests that management efforts at shallow depths will have little impact on deeper populations, which may serve as a refuge from culling efforts. Finally, I show that farming damselfish display different anti-predator behaviours across sites with varying structural complexity. A greater field of view led to more cautious behaviour, while refuge availability had little apparent effect. This suggests that changes in the visual landscape of a reef can shape how fish perceive risk and influence predator-prey dynamics. By examining the role of refuges at multiple ecological levels, from individuals to entire communities, this work provides new insights and suggests future research directions, emphasising the need to acknowledge and integrate refuges into conservation strategies.